A resurrection study reveals limited evolution of thermal performance in response to recent climate change across the geographic range of the scarlet monkeyflower. (24th June 2020) - Wooliver, Rachel; Tittes, Silas B.; Sheth, Seema N.
Abstract: Evolutionary rescue can prevent populations from declining under climate change, and should be more likely at high‐latitude, "leading" edges of species' ranges due to greater temperature anomalies and gene flow from warm‐adapted populations. Using a resurrection study with seeds collected before and after a 7‐year period of record warming, we tested for thermal adaptation in the scarlet monkeyflower Mimulus cardinalis . We grew ancestors and descendants from northern‐edge, central, and southern‐edge populations across eight temperatures. Despite recent climate anomalies, populations showed limited evolution of thermal performance curves. However, one southern population evolved a narrower thermal performance breadth by 1.31°C, which matches the direction and magnitude of the average decrease in seasonality experienced. Consistent with the climate variability hypothesis, thermal performance breadth increased with temperature seasonality across the species' geographic range. Inconsistent with performance trade‐offs between low and high temperatures across populations, we did not detect a positive relationship between thermal optimum and mean temperature. These findings fail to support the hypothesis that evolutionary response to climate change is greatest at the leading edge, and suggest that the evolution of thermal performance is unlikely to rescue most populations from the detrimental effects of rapidly changing climate.